Enhancement of water-gas injection technology for oil reservoirs - Tenik Ya. T. (НТУ «ДП», 2025)
The history of oil utilization by humanity dates back to ancient times, with industrial extraction beginning nearly two centuries ago. Despite advancements in renewable energy, oil remains a key global energy source for decades to come. Oil recovery factors typically range from 25% to 35% due to geological variations, leaving most fluids trapped in reservoirs. This poses a major challenge in the oil industry, prompting the development of enhanced oil recovery (EOR) methods. Waterflooding, discovered in the 19th century in the USA, is the most common due to its low cost, simplicity, and water availability. However, it fails to achieve high recovery rates, often resulting in increased water cut and additional preparation costs [1, 2].
Keywords: водяний газ; нафтові роли; нафтова промисловість